Homozygous Deletion of the CFTR Gene Caused by Interstitial Maternal Isodisomy in a Peruvian Child with Cystic Fibrosis - Vásquez Sotomayor, Flor; Abarca-Barriga, Hugo Hernán (Journal of Pediatric Genetics, 2019)
We report the first case in Peru of cystic fibrosis caused by a homozygous deletion of the cystic fibrosis transmembrane conductance regulator (CFTR) gene. A 10-month-old child who presented with meconium ileus and pancreatic insufficiency was tested for cystic fibrosis. Both parents of the child are of Peruvian background, are nonconsanguineous, and have no personal or family history of the disease. Chromosome microarray analysis revealed a homozygous deletion of the CFTR gene on chromosome 7 (7q31.2) within a maternally derived 12.8-Mb region of loss of heterozygosity with deletion of a region that includes the CFTR gene. Parental testing confirmed this finding. This case highlights the great importance of molecular testing and the study of chromosomal rearrangements in reaching a correct diagnosis and providing proper genetic counseling to the affected families.
Keywords: cystic fibrosis; CFTR gene; chromosome microarray analysis; copy number variation; loss of heterozygosity; uniparental disomy